MODIFIKASI FOTOBIOREAKTOR HEMAT ENERGI DENGAN LIGHT EMITTING DIODE (LED) UNTUK MENINGKATKAN POPULASI Chlorella spp. DALAM UPAYA PEMENUHAN PAKAN ALAMI LARVA IKAN BANDENG - Rosady, Siti Duratun Nasiqiati; Kusumadewayanti, Esthi; Amanatin, Dwi Riesya; Nasikhin, Roksun; Fiqar, Tegar Palyus (REKAPANGAN, 2012)
Fotobioreaktor experiments with fluorescent light sources have been reported can increase the efficiency of photosynthesis in fitoplankton. The results of such experiments show that the density of the fitoplankton culture in fotobioreaktor in line with increasing the intensity of light . Chlorella vulgaris grown in fotobioreaktor with sea water and walne medium. The trial was done with treatment intensity variations  of  different  light  sources, namely  light  source  LED  1  X  3  watt  LED  2  X  3  Watts.  Fotobioreaktor placed in a box by a distance of 10 cm from a source of light. Fotobioreaktor used as a comparison with Neon light source 1 X 8 Watts and Neon 2 X 8 watts. Two-factor ANOVA analysis showed that (p> 0,05), it means there are no interaction effect a between the sides and the source of light . Fotobioreaktor led light source with 1 x 3 watts capable of producing Chlorella vulgaris density equal  to  fotobioreaktor  source  of  a  fluorescent  with  2  x  8  watts.  The  result  indicates  fotobioreaktor light source  with  power  3  watt more  efficient  in  the  use  of electrical  energy  to produce  a  density  of Chlorella  vulgaris.   This  provides  an  indication  that  fotobioreaktor  with  energy-efficient  LED  light source and are able to increase the density of Chlorella Vulgaris.Keyword: Chlorella Vulgaris, Led Emitting Diode, Economical Energ